Book Review: Economic Restructuring and Family Wellbeing in Rural America - Mary Ann Demi (Journal of Research in Rural Education, 2012)
With the approaching presidential election, the nation's economy is not only a topic for intense debate among politicians but also a major source of angst for individuals who are counting on our nation's leaders to advance policies that will provide employment opportunities offering wages that can adequately sustain a living wage and promote their family's wellbeing. The success for any economic plan will require that our politicians understand and address the complexity and relationship between employment and community conditions as well as the health, education and family support systems that need to co-evolve in order to establish and maintain employment opportunities with access to a ready and able workforce. This is a difficult task for politicians as there is often tension between developing national economic policy and family support policies. Yet, the two are essential to each other.